MEMBEKALI PELAYAN PASTORAL: PELATIHAN KONSELOR SEBAGAI LANGKAH MAJU DALAM PENINGKATAN KUALITAS PELAYANAN JEMAAT - Brek, Yohan; Lombogia, Randy. A.P.P (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The results of this research show that counselor training significantly increases participants' knowledge regarding the principles of pastoral counseling, listening skills, empathetic attitudes and the ability to apply pastoral counseling methods and techniques in real situations. Apart from that, this program was also successful in raising participants' awareness of the importance of a holistic approach in serving the congregation which considers physical, mental, social and spiritual aspects. The results and conclusions of this research state that counselor training is a vital step forward in efforts to improve the quality of congregational services, providing a stronger foundation for counselors to support congregation members in life's challenges with a quality faith perspective. Keywords: The results of this research show that counselor training significantly increases participants' knowledge regarding the principles of pastoral counseling, listening skills, empathetic attitudes and the ability to apply pastoral counseling methods and techniques in real situations. Apart from that, this program was also successful in raising participants' awareness of the importance of a holistic approach in serving the congregation which considers physical, mental, social and spiritual aspects. The results and conclusions of this research state that counselor training is a vital step forward in efforts to improve the quality of congregational services, providing a stronger foundation for counselors to support congregation members in life's challenges with a quality faith perspective.